2005
DOI: 10.1007/s11259-005-3684-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chemistry and Histological Properties of Wild and Cultured Sea Bass (Dicentrarchus labrax) in the North Adriatic Sea

Abstract: Histological and biochemical procedures were employed to study liver histomorphology and plasma levels of aspartate aminotransferases (AST), alanine aminotransferase (ALT), triglyceride (TRIG), cholesterol (CHOL), glucose (GLU) and total protein (TP) in cultured (CSB) and wild sea bass (WSB) (Dicentrarchus labrax) from the northern part of the Adriatic Sea. Histopathological changes in liver included varying degrees of infiltration and lipid degeneration of hepatocytes in examined cultured fish. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 10 publications
15
89
4
2
Order By: Relevance
“…An increased blood glucose and protein level was recorded in L. calcarifer, this may probably be due to an increased depletion of liver glycogen (Ojolick et al 1995). Our findings confirm those of Coz-Rakovac et al (2005) who reported a significantly elevated glucose level in farmed Dicentrarchus labrax as compared to the wild ecosystem. Strange (1980) also reported that blood glucose level may decrease with increasing water temperature in channel catfish.…”
Section: Statistical Studysupporting
confidence: 92%
See 2 more Smart Citations
“…An increased blood glucose and protein level was recorded in L. calcarifer, this may probably be due to an increased depletion of liver glycogen (Ojolick et al 1995). Our findings confirm those of Coz-Rakovac et al (2005) who reported a significantly elevated glucose level in farmed Dicentrarchus labrax as compared to the wild ecosystem. Strange (1980) also reported that blood glucose level may decrease with increasing water temperature in channel catfish.…”
Section: Statistical Studysupporting
confidence: 92%
“…Strange (1980) also reported that blood glucose level may decrease with increasing water temperature in channel catfish. Blood glucose level may vary according to season and water temperature, and glucose concentration in fish decreases with age and size (Coz-Rakovac et al 2005). The increased plasma protein concentration can be caused by structural liver alternations that reduce aminotransferase activity, with concurrent reduction in deamination capacity (Kavadias et al 2004).…”
Section: Statistical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The control fish serum protein was 6.23g/dl and (experimental fish) fishes exposed to 0.16% was 8.43 gm/dl. According to Rakovac et al, (2005), increased concentrations of total protein can be caused by structural liver alterations reducing aminotransferase activity impaired control of fluid balance. Serum Kuck et al, (2012), also reported that there was increase in total protein as salinity increases.…”
Section: Resultsmentioning
confidence: 99%
“…Bender et al [17] reported that small differences in body size do not result in significant changes in cortisol production and metabolism, which are related to elevated levels of cholesterol. Xu and Cao [18] and Coz-Rakovae et al [19] also reported the elevated levels of cholesterol in farmed fishes. Furthermore, Yousafzai and Shakoori [20] reported that aquatic pollution leads to the elevated tissue cholesterol in fish.…”
Section: Discussionmentioning
confidence: 99%